Targeted Gene Editing in Porcine Spermatogonia - Webster, Dennis; Bondareva, Alla; Solin, Staci; Goldsmith, Taylor; Su, Lin; Lara, Nathalia de Lima e Martins; Carlson, Daniel F.; Dobrinski, Ina (Frontiers in Genetics, 2021)
To study the pathophysiology of human diseases, develop innovative treatments, and refine approaches for regenerative medicine requires appropriate pre-clinical models. Pigs share physiologic and anatomic characteristics with humans and are genetically more similar to humans than are mice. Genetically modified pigs are essential where rodent models do not mimic the human disease phenotype. The male germline stem cell or spermatogonial stem cell (SSC) is unique; it is the only cell type in an adult male that divides and contributes genes to future generations, making it an ideal target for genetic modification. Here we report that CRISPR/Cas9 ribonucleoprotein (RNP)-mediated gene editing in porcine spermatogonia that include SSCs is significantly more efficient than previously reported editing with TALENs, and allows precise gene editing by homology directed repair (HDR). We also established Homology Mediated End Joining (HMEJ) as a second approach to targeted gene editing to enable introduction of larger transgenes and/or humanizing parts of the pig genome for disease modeling or regenerative medicine. In summary, the approaches established in the current study result in efficient targeted genome editing in porcine germ cells for precise replication of human disease alleles.